PENGELOLAAN PAJAK HOTEL DAN PAJAK RESTORAN - Simbolon, Sahat Pardomuan; Heriyanto, Meyzi; Yuliani, Febri (Jurnal Ilmu Administrasi Negara, 2019)
Management of Hotel Taxes and Restaurant Taxes. This study aims to find out hotel and restaurant taxes in order to increase the Regional Original Income Pelalawan District. This type of research is qualitative. The research informant is Head of Secretary of BPKAD, Head of Division and Taxpayer. Technical data are interviews and documentation studies. Data analysis using interactive models. The results showed that the constitution of hotel and restaurant tax management on the Realization of Pendapatan Asli Daerah (PAD) is still very minimum.